Assessing the Impact of Knowledge and Attitudes on Preventive Behaviors for Tuberculosis Transmission in Families of Pulmonary TB Patients: A Study in the Sempaja Health Care Center - Kusumawati Rahayu, Hanis; Rahma, Khairunnida; Dewi Puspita A, Fitria; Anggita Wikaningtyas, Dila; Nur Qolbiyah, Fadzilah; Lutfi Salsabila, Vaya; Lelyana Novitasari, Putri; Abelio Dirgusma Dalung, Yohanes (Mulawarman International Conference on Tropical Public Health, 2025)
Tuberculosis (TB) remains a global health issue, with cases increasing from 10 million in 2020 to 10.6 million in 2022. Indonesia ranks second in the world for TB cases, accounting for 10% of global cases. The Ministry of Health of Indonesia reported 658,543 TB cases in 2023, and in East Kalimantan, there were 15,369 cases, with an estimated 2,081 new pulmonary TB cases. In Samarinda, TB cases increased from 1,456 in 2021 to 2,167 in 2022. Aim of this study to find the relationship between knowledge and attitude toward preventive behavior in the transmission of pulmonary TB among families of patients in the Sempaja Health Center This Research was an analitic observational methods with a cross sectional approach. The Population of this study was active pulmonary Tuberculosis patient in 2023 (40 patient). Sample of this research must be met the inclusion criteria. Characteristics of Family Members of Pulmonary Tuberculosis (TB) Patients based on occupation: Most of respondents were actively employed (70%), and the majority had completed high school education (80%). The age distribution showed that most participants were aged 31–40 years (45%). Regarding gender, the majority of participants were female (70%). It was found that 65% respondents had a good level of knowledge about pulmonary Tuberculosis. There were 55% respondents demonstrated good preventive behaviors against pulmonary TB. There was a significant corelation between knowledge and preventive behaviour (p= 0.022). Most families of pulmonary tuberculosis (TB) patients in the Sempaja Health care Center have good knowledge and positive attitude toward pulmonary TB. Engage in good preventive behaviors against pulmonary TB. There was a significant relationship between knowledge, attitude and preventive behaviors regarding TB transmission in the Sempaja Health care Center.